Implementation of a PBL Model Based on a Process Differentiation Approach to Improve High School Students’ Problem-Solving Skills in the Topic of Static Fluids - Karimah Fajriani; Lina Aviyanti; Winny Liliawati (Jurnal Pijar MIPA, 2026)
Problem-solving skills are considered essential competencies in 21st-century physics education, yet many students experience difficulties in solving physics problems effectively. This study aimed to examine the effectiveness of applying a Problem-Based Learning (PBL) model integrated with a process differentiation approach in enhancing senior high school students’ problem-solving skills on the topic of static fluids. The study employed a quantitative quasi-experimental design with a nonequivalent control group format. Participants consisted of 68 eleventh-grade students from a public senior high school in Bandung, divided into an experimental group and a control group. In the experimental class, process differentiation was implemented through varied learning activities tailored to students’ learning-style characteristics. Data were gathered through essay-based tests designed to measure problem-solving skills and were analyzed using N-Gain and Mann–Whitney tests. The findings revealed that students in the experimental class showed greater improvement, with an average N-Gain score of 0.51, compared to 0.31 in the control class. In addition, the calculated Cohen’s d value of 1.1 indicated a strong practical effect of the treatment. The results suggest that integrating process differentiation into the PBL model effectively improves students’ problem-solving skills in learning about static fluids. The findings contribute to the growing body of evidence supporting the integration of differentiated instruction with Problem-Based Learning as an effective pedagogical approach for physics education.